(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Energy security and energy diversification have become key components of the European Union’s response to the Russo-Ukraine war. While leveraging Green Deal instruments to boost renewable energy investment and replace coal and to some extent nuclear power generation, the Union has not been fully successful in its goals to secure energy independence from Russian energy supplies. The dependency on natural gas persists and has proven many of its critics wrong as the EU is currently importing gas from USA, Algeria, Norway and even Russia through various intermediaries. With domestic natural gas production decreasing, looking back to historic obstructions to developing new sources is justified from a national and regional security perspective. This article studies the anti-shale gas movements in the early and mid-2000s in Eastern Europe, which culminated in almost blanket bans on developing shale gas fields. Looking back at these events through the lens of a type of information warfare called reflexive control finds plausible evidence that such may have been applied in order for Russia to block or delay Eastern European efforts for energy security and energy diversification. Tracking the political behaviour and stances of the anti-shale movement leaders in the early and mid-2000s points to them holding a diverse array of opinions and contemporary positions concerning the Russo-Ukraine war and dealing with Russia in the area of energy today. This suggests that foreign information warfare and information interference could have targeted very basic elements and assumptions in the decision-making processes of civil society and state actors, which do not necessarily depend on their political perceptions of Russia. It is therefore possible to lay out and at least partially confirm a hypothesis that a reflexive control operation that substitutes and modifies such processes with new information concerning exaggerated and manipulated shale gas development risks might have been carried out by foreign state or non-state interested parties.